Analyzing Dating Application Adoption Towards Behavioral Intention Using A Utaut2 (Case Study: Premium Bumble User In Indonesia) - Setiawan, Laudza Tsabitul Azmi; Febrianta, Mochamad Yudha (eProceedings of Management, 2023)
The Covid-19 pandemic has changed the current style of socializing, and dating applications have become an interesting topic of conversation in Indonesia. Rakuten Insight states that interactions on dating apps increased by 32% during Covid-19, and dating app usage increased by 19% over one year. Bumble is one of the biggest dating apps in the world. The purpose of this study was to investigate the factors associated with technology acceptance and use of the Bumble application. The research framework used in this study is UTAUT2. Data collection was processed using a questionnaire technique which was distributed to all Bumble users who are domiciled in Indonesia. Data analysis will use SmartPLS 3.2.9 which produces outer model testing and inner model testing. Descriptive analysis in this study is needed to understand more deeply about the characteristics of the respondents and their assessment of Bumble. The results show that there are five significant factors that influence Use Behavior and Behavioral Intention of Bumble users in Indonesia, namely Performance Expectancy, Social Influence, Facilitating Conditions, Price Value, and Habit and have a significant positive effect on Behavioral Intention. Meanwhile, Behavioral Intention and Habit have a significant positive influence on Use Behavior.Keywords-Bumble, UTAUT2, use behavior, behavior intention, Indonesia